The Result of Halal Orientation Strategy on Green Supply Chain Performance in the Fast-Food Industry - TAN, LAY HONG; Ahmat, Norunnajjah; Jasmin, Nur Farah Ain (Journal of Human Capital Development (JHCD), 2025)
Halal orientation strategy refers to business practices that align with the religious requirements and preferences of Muslim consumers. Given the growing demand for halal fast food, concerns have emerged regarding halal compliance across supply chains. This study examines how halal orientation strategies influence green supply chain performance in the fast-food industry. The study considers factors related to materials and ingredients, production processes, storage, transportation and logistics, halal culture, and social responsibility. Data were collected from approximately 150 respondents representing fast-food businesses using a structured questionnaire. Partial Least Squares Structural Equation Modelling (PLS-SEM) via SmartPLS 4 was employed to analyse the relationships between the constructs. The findings indicate that social responsibility and halal-oriented operational practices significantly enhance green supply chain performance. The study offers valuable insights into how halal orientation strategies can simultaneously support religious compliance and environmental sustainability in the fast-food industry.